Fostering Democracy: Unlocking Pakistan’s Potential For A Secure And Prosperous Future - Dr. Waseem Ullah , Dr. Hassina Bashir , Imran Ullah Khan Marwat , Dr. Umar Zad , Ambrin Khurshid (Migration Letters, 2024)
Democratic development in Pakistan is critical to political stability, human rights, economic growth, accountability and peace. For a country, which has been going back and forth between democratic and authoritarian regimes, a functional democracy is the need of the hour. It enables the peaceful handover of power by way of free elections and minimises political instability while making governance legitimate. It facilitates participatory consultation whilst also embracing diversity perspectives into decision-making. Democracy ensures that the voice of the citizens is heard, while also fostering human rights and social justice for minorities and discriminated groups. Such inclusiveness helps cater to the ethnic and religious diversity of the country, thereby potentially reducing social tension and creating unity. Governments that are democratically elected and which function efficiently provide an environment where investment can grow, and this leads to economic stability. This means allowing policy taking into account demographic demand, for example, to foster sustainable growth. In addition, democratic governance fosters transparency and accountability thereby playing a significant role in fighting corruption and promoting effective resource utilization. Ultimately, democratic development is a bulwark against problems that breed conflict and insecurity including unaddressed grievances, or authoritarianism that propels extremism. In short, democratic development is so important to the future of Pakistan because it offers a pathway to security, rights protection, economic growth, accountability and peace. Located in South Asia, Pakistan has emerged as a key player on the international stage due to its geographical location and influence; however it is a challenging environment characterized by regional extremism.